Treatment of Hypertension: Favourable Effect of the Twice-Daily Compared to the Once-Daily (Evening) Administration of Perindopril and Losartan - Ipoly Szauder; Eszter Csajági; Zsuzsanna Major; Gabor Pavlik; Gabriella Ujhelyi (Karger Publishers, 2015)
Background/Aims: Little is known about the effect of twice daily administration of same dose of ACE inhibitor and ARB on the diurnal/nocturnal blood pressure (BP) ratio. We aimed to assess the effect of two widely used long-acting drugs: perindopril and losartan in the treatment of hypertension comparing the once-daily (evening) vs. twice-daily (morning and evening) administration with the same daily doses. Methods: Untreated primary hypertensive patients without complaints (a total of 164: 65 men, 99 women, 55.7±13.7 years of age, 41-41 patients per treated groups) were selected with non-dipper phenomenon, estimated by diurnal index (DI) Results: The mean BP, the percent time elevation index, and the hyperbaric impact decreased in both drug groups. Significant difference was observed in the DI in the case of twice-daily administration vs once-daily evening dosing. Conclusions: The twice-daily administration with the same daily dose of perindopril or losartan seems to be more effective compared to the once daily evening administration in eliminating the non-dipper phenomenon. According to some authors the non-dipping phenomenon increases cardiovascular risk, while others are of the opinion that the association of non-dipping with cardiovascular events does not necessarily mean that selective treatment of non-dipping improves cardiovascular outcomes.